An audit of patients referred for nerve conduction study in a tertiary care hospital in Bangladesh - Chowdhury, Rajib Nayan; Hussain, Md Enayet; Islam, Md Nahidul; Hosen, Mostafa; Khan, AFM Al Masum; Mian, Md Ferdous; Hasan, ATM Hasibul; Mondal, Md Badrul Alam; Mohammad, Quazi Deen (Journal of Dhaka Medical College, 2015)
Background: To examine the pattern and burden of neurologic disorders at electrophysiology lab of a tertiary care centre. Methodology: This retrospective chart review was carried out from the records and notes of electrophysiology lab in National Institute of Neurosciences and Hospital (NINS) from January to December 2013. A total of 1372 patients were evaluated with nerve conduction study (NCS) and electromyography (EMG) during this period. Result: Majority of the patients (67.6%) presented after forty with a mean age at presentation of 48.11±17.3 years. The male patients (55.2%) predominated. Carpal tunnel syndrome (CTS) was the most common condition (19.2%) observed, followed by different form of polyneuropathy namely Guillain Barre Syndrome (GBS) (6.04% with 50% being Acute inflammatory demyelinating polyneuropathy (AIDP), chronic inflammatory demyelinating polyneuropathy (CIDP) (3.27%), sensory motor polyneuropathy 3.13% and multifocal acquired motor axonopathy (MAMA) 2.55%. Though plexopathy and radiculopathy were rare (1.09 and 0.94% respectively), anterior horn cell disease was not that uncommon (8.73%). Disorders of muscle and neuromuscular junction (myasthenia gravis) were seen in 5.1% and 1.89% patient. Other various conditions (e.g. stroke, cerebral palsy, myelopathy) were observed in 10.05%. NCS and EMG were found to be normal in 270 patients (19.6%). Conclusion: Wide ranges of neurological problems are often referred to electrophysiology lab. Where ever the facilities and expert hands are available, these tests can help in diagnosing and classifying these cases. DOI: http://dx.doi.org/10.3329/jdmc.v23i1.22703 J Dhaka Medical College, Vol. 23, No.1, April, 2014, Page 102-108